A Dual Role of DDX3X in dsRNA-Derived Innate Immune Signaling - Kwon, Juntae; Choi, Hyeongjwa; Han, Cecil (Frontiers in Molecular Biosciences, 2022)
DEAD-Box Helicase 3 X-Linked (DDX3X) is essential for RNA metabolism and participates in various cellular processes involving RNA. DDX3X has been implicated in cancer growth and metastasis. DDX3X is involved in antiviral responses for viral RNAs and contributes to pro- or anti-microbial responses. A better understanding of how human cells regulate innate immune response against the viral “non-self” double-stranded RNAs (dsRNAs) and endogenous viral-like “self” dsRNAs is critical to understanding innate immune sensing, anti-microbial immunity, inflammation, immune cell homeostasis, and developing novel therapeutics for infectious, immune-mediated diseases, and cancer. DDX3X has known for activating the viral dsRNA-sensing pathway and innate immunity. However, accumulating research reveals a more complex role of DDX3X in regulating dsRNA-mediated signaling in cells. Here, we discuss the role of DDX3X in viral dsRNA- or endogenous dsRNA-mediated immune signaling pathways.